A novel NTRK1 splice site variant causing congenital insensitivity to pain with anhidrosis in a Chinese family - Sun, Ling; Dai, Jin; Zhang, Yuan; Zhou, Lijun; Ren, Yaqiong; Wang, Hongying (Frontiers in Genetics, 2024)
Background: Congenital insensitivity to pain with anhidrosis (CIPA, OMIM #256800), also known as hereditary sensory and autonomic neuropathy type Ⅳ (HSAN-IV), is a rare autosomal recessive disorder characterized by recurrent episodic fevers, anhidrosis, insensitivity to noxious stimuli, selfmutilating behavior and intellectual disability. CIPA can be caused by the variants in NTRK1 gene, which encodes a high-affinity tyrosine kinase receptor for nerve growth factor. To ascertain the hereditary cause of a patient with CIPA accompanied by the additional symptoms of mild growth retardation, prone to fracture, underdeveloped nails of fingers and toes, irregular tooth alignment, enamel hypoplasia, postoperative wound healing difficulty, hand and limb deformity, and dislocation of hip joint, whole exome sequencing was used and revealed a compound heterozygous variant in NTRK1. Methods: DNA was extracted from peripheral blood samples of pediatric patients and their parents, and subjected to comprehensive analysis using whole-exome sequencing (WES), followed by verification of variant sites in the NTRK1 gene through Sanger sequencing. To elucidate the functional impact of the newly discovered variants, an in vitro experimental system was established. Splicing analysis was conducted using PCR and Sanger sequencing, while expression levels were assessed through qPCR and western blot techniques. Results: One hotspot variant c.851-33T>A(ClinVar ID: 21308) and a novel variant c.850+5G>A(ClinVar ID:3069176) was inherited from her father and mother, respectively, identified in the affected individuals. The c.850+5G>A variant in NTRK1 resulted in two forms of aberrant mRNA splicing: 13bp deletion (c.838_850del13, p.Val280Ser fs180) and 25bp deletion (826_850del25, p.Val276Ser fs180) in exon 7, both leading to a translational termination at a premature stop codon and forming a C-terminal truncated protein. The expression of two abnormal splicing isoforms was decreased both in the level of mRNA and protein. Conclusion: In conclusion, this study elucidated the genetic cause of a patient with CIPA and identified a novel variant c.850+5G>A in NTRK1, which broadened the and enriched the NTRK1 mutation spectrum.